ANALYSIS OF THE MARKETING MIX STRATEGY ON PURCHASE INTENTIONS AT MINIMARKET ALFA M LEBO SIDOARJO - Dewi , Grace Citra; Purwono, Bambang Sugiyono Agus; Bernardus, Denny; Efrata, Tommy Christian; Yulianah, Yulianah (Sean Institute, 2023)
This research was conducted to analyze the influence of the marketing mix strategy on consumer repurchase intention. This research is based on the widespread presence of shopping centers, especially in the retail section. This requires business people to know more about the right marketing mix used to influence consumer purchase intentions in order to maintain the smooth running of their business. Thus, the purpose of this research is to examine how the marketing mix strategy at Alfa M Lebo Sidoarjo affects shoppers' propensity to make a purchase. This study employs a quantitative approach, and it is a descriptive, causal study. Non-probability sampling with incidental sampling was utilized for this investigation, and its total sample size was 100. SPSS 22.0 for Windows is utilized for both descriptive and simple linear regression analysis of the data. Findings indicated that Alfa M Lebo Sidoarjo's marketing mix strategy significantly influenced shoppers' intent to make a purchase. Where the marketing variable received a good response with a score of 82.54 percent and the purchase intention variable was also in the good category, namely 77.86 percent. Overall, the marketing mix variable has enough influence on purchase intention, which is equal to 46.0 percent.